Corporate Governance and Equity Finance: Evidence from the Indonesian Manufacturing Companies Listed in the IDX in 2016-2018 - Yuan Natalia Puteri Wibowo; Caroline Angela (iBuss Management, 2020)
Business collapses due to a weak system of corporate governance have made corporate governance become a critical global policy agenda. In fact, good quality of corporate governance has been proven to bring benefits to various firm’s aspects, including access to equity finance. Despite its importance, limited studies have analyzed the correlation between corporate governance and equity finance using Indonesian firms as a subject. Thus, in this study, the researchers aim to know the impact of corporate governance on equity finance with firm size, firm age, profitability, growth potential, and asset tangibility as the control variables. Specifically, the researchers collected data from 85 manufacturing companies listed in the IDX during 2016-2018 that passed the purposive sampling criteria. The data collected were further analyzed using multiple linear regression. Based on the statistical processes, it was found that only profitability, growth potential, and asset tangibility affect equity finance significantly. On the other hand, corporate governance, firm size, and firm age do not have any significant relationship with equity finance.Keywords: Equity Finance, Corporate Governance, Profitability, GrowthPotential, Asset Tangibility